Activists and Incumbents Structuring Change: The Interplay of Agency, Culture, and Networks in Field Evolution - van Wijk, Jakomijn; Stam, Wouter; Elfring, Tom; Zietsma, Charlene; den Hond, Frank (Academy of Management Journal, 2013)
We examine organizational field change instigated by activists. Contrary to existing views emphasizing incumbent resistance, we suggest that collaboration between incumbents and challenger movements may emerge when a movement's cultural and relational fabric becomes moderately structured, creating threats and market opportunities but remaining permeable to external influence. We also elucidate how lead incumbents' attempts at movement cooptation may be deflected through distributed brokerage. The resulting confluence of cultural and relational “structuration” between movement and field accelerates the pace but dilutes the radicalness of institutional innovation, ensuring ongoing, incremental field change. Overall, this article contributes to the emergent literature on field dynamics by uncovering the evolution and outcomes of collaborative work at the intersection of social movements and incumbent fields.